INSTRUMENTS OF STATE REGULATION OF EXPORTS UNDER THE CONDITIONS OF MARITAL STATE - SMENTYNA, Nataliia (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article analyses the impact of the war in Ukraine on national entrepreneur’s export activity as the simplest form of their foreign economic activity. The general trends in the Ukrainian export of goods and services were revealed. For example, in the context of changes in geographical structure, the only available direction of Ukraine’s foreign trade now is the west. Also, the unevenness of the export reduction by the sectors of the national economy was noted. The article shows the present of export reduction in all sectors of Ukraine economy. The article defines the challenges faced by national entrepreneurs due to the introduction of customs-tariff and non-tariff state regulation of foreign economic activity as by the Ukrainian government and by global market players. Among the challenges, the following are identified: closing the markets of the aggressor country and the needs of finding new sales markets for nationally produced products; problems with logistics; changes in the list of goods whose export is subject to quotas and licensing. The article shows the role of administrative economic instruments pursued to prevent food insecurity. Attention is focused on such an instrument of state regulation of foreign economic activity as the customs duty. The transformation of this state regulation instrument role from a kind of barrier to entering world markets into a preference for supporting Ukrainian business in the difficult conditions of war has been shown. Due to the weakening of the protective function of customs duties, the importance of non-tariff regulation tools in the form of technical barriers, subsidies, subsidies, currency regulation tools, etc. has been emphasized. The instruments of government financial support of Ukrainian entrepreneurs with export potential have been determined. The main of these tools are: informing businesses about changes in the legislative framework of foreign economic activity from the State Institution "Office of Entrepreneurship Development and Reforms"; stimulating export expansion through financial risk insurance; the possibility of obtaining grant support within the framework of the implementation of the government initiative "is a Job"; consulting support from the Chamber of Commerce and Industry.